Finance of small bio-pharmaceutical industry in Finland: Descriptive analysis - Raine Hermans (The Research Institute of the Finnish Economy (ETLA), 2004)
This study investigates the capital and ownership structures of small and medium-sized pharmaceutical-related biotechnology firms (bio-pharmaceutical companies) in Finland. These structures are also analyzed taking into account general characteristics and intangible assets of the business activities in the industry. Relatively young companies are typically owned by persons that are active in business, private venture capital companies, and government institutions. Older firms are mostly owned by other non-financial companies. The major capital loan supplier has been TEKES, the National Technology Agency of Finland. Equity finance from private venture capital companies and governmental sources has supported growth in research and development activities in the companies examined. However, the companies owned mostly by non-financial companies have been able to generate relatively high sales. These firms are also anticipated to have the highest sales potential over the next 5 years. The results here are contrasted with explanations of capital structure found in the literature. No single theory can by itself explain the capital and ownership patterns within Finnish bio-pharmaceutical companies. Instead, the literature suggests many explanations for the observed ownership patterns. For example, different patterns can be related to the owners' willingness to monitor the managers and support activities with high earning prospects. – Biotechnology ; capital structure ; finance ; intangible assets ; pharmaceutical industry – – Tämä tutkimus selvittää pienten ja keskisuurten lääkealan bioteknologiayritysten rahoitusrakenteita Suomessa. Lisäksi rahoitusrakenteiden merkitystä analysoidaan alan liiketoiminnan erityispiirteiden kannalta. Alan rahoitusrakenteille on tyypillistä, että nuorten yritysten merkittävimpiä omistajia ovat liiketoiminnassa mukana olevien henkilöiden lisäksi yksityiset pääomasijoitusyhtiöt sekä julkisen sektorin pääomasijoitusinstituutiot. Iäkkäämpien yritysten suurimpina omistajina ovat toiset yritykset. Merkittävin yksittäinen pääoma- ja muiden lainojen tarjoaja on ollut Tekes. Yksityisten pääomasijoitusyhtiöiden ja julkisen sektorin toimijoiden osakerahoitus on tukenut yritysten tutkimus- ja kehitystoiminnan kasvua. Kuitenkin muiden kuin rahoitusalan yritysten omistamat bioteknologiayritykset ovat onnistuneet saamaan aikaan myyntiä muita yrityksiä enemmän. Näillä yrityksillä odotetaan olevan huomattavin myynnin myyntipotentiaali myös lähitulevaisuudessa (5 vuoden kuluessa). Tuloksia peilataan myös rahoitusrakenteiden syitä selittävään kirjallisuuteen. Yleispätevää lääkealan bioteknologiayritysten rahoitusrakenteita selittävää teoriaa ei kirjallisuudesta yksiselitteisesti löydy. Sen sijaan yksittäisille aineiston komponenteille löytyy luontevia selityksiä esim. siitä miten eri tavoin omistajat voivat pyrkiä valvomaan yritysjohdon käyttäytymistä ja tukemaan sellaista toimintaa, joka synnyttää tulevaisuuden tuotto-odotuksia. Deskriptiivisen analyysin perusteella “käänteinen nokkimisjärjestysteoria” vaikuttaa lupaavalta ehdokkaalta selittämään vieraan pääoman ehtoisen ja oman pääoman ehtoisen rahoituksen suhdetta t&k-intensiivisten biotekniikkayritysten kohdalla.
Keywords: 330; aineeton varallisuus; biotekniikka; lääketeollisuus; pääomasijoitukset; Pharmazeutische Industrie; Klein- und Mittelunternehmen; Unternehmensfinanzierung; Finnland